2019
DOI: 10.3389/fimmu.2019.02552
|View full text |Cite
|
Sign up to set email alerts
|

High Nuclease Activity of Long Persisting Staphylococcus aureus Isolates Within the Airways of Cystic Fibrosis Patients Protects Against NET-Mediated Killing

Abstract: Staphylococcus aureus is one of the first and most prevalent pathogens cultured from the airways of cystic fibrosis (CF) patients, which can persist there for extended periods. Airway infections in CF patients are characterized by a strong inflammatory response of highly recruited neutrophils. One killing mechanism of neutrophils is the formation of neutrophil extracellular traps (NETs), which capture and eradicate bacteria by extracellular fibers of neutrophil chromatin decorated with antimicrobial granule pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…The relatedness of such clones with different spa-types, but very similar repeat successions was verified by pulsed-field gel electrophoresis (Kahl et al, 2005), multi-locus sequence typing (MLST) (Hirschhausen et al, 2013) or WGS (Schwartbeck et al, 2016). In different studies, we now confirmed that persistent S. aureus isolates persisting in the airways of CF patients, which are assigned to the same or related spa-types, which differed in their VNTR region by various mutations as outlined above, were confirmed to belong to the same clone by WGS (Schwartbeck et al, 2016;Langhanki et al, 2018;Herzog et al, 2019). Therefore, it seems that spa-sequence typing is a suitable method to analyze the relatedness of S. aureus isolates.…”
Section: Introductionsupporting
confidence: 66%
“…The relatedness of such clones with different spa-types, but very similar repeat successions was verified by pulsed-field gel electrophoresis (Kahl et al, 2005), multi-locus sequence typing (MLST) (Hirschhausen et al, 2013) or WGS (Schwartbeck et al, 2016). In different studies, we now confirmed that persistent S. aureus isolates persisting in the airways of CF patients, which are assigned to the same or related spa-types, which differed in their VNTR region by various mutations as outlined above, were confirmed to belong to the same clone by WGS (Schwartbeck et al, 2016;Langhanki et al, 2018;Herzog et al, 2019). Therefore, it seems that spa-sequence typing is a suitable method to analyze the relatedness of S. aureus isolates.…”
Section: Introductionsupporting
confidence: 66%
“…Neutrophils are key inflammatory cells in the immune system's arsenal, and the dysregulation of approximately 90 of their genes related to the production of cytokines, chemokines, interleukin receptors, colony-stimulating factors and intracellular signalling molecules dramatically contributes to the inflammatory phenotype found in CF [118]. This dysregulation may also lead to an increased risk of infection taking place in the lungs by P. aeruginosa [119,120], Staphylococcus aureus [121] and Burkholderia cepacia complex [122].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Polymorphonuclear leukocytes (PMNs) such as neutrophils are key players of the innate immune system that eradicate invading pathogens by either neutrophil extracellular trap formation (Brinkmann et al, ; Herzog et al, ), phagocytosis and intracellular degradation in oxidised phagosomes or release of reactive oxygen species (ROS) and reactive nitrogen species during oxidative burst (Nordenfelt & Tapper, ). Furthermore, PMNs contain high amounts of antimicrobial proteins that are secreted upon cell activation, among them the calcium‐, manganese‐, and zinc‐sequestering protein complex S100A8/A9 (also called myeloid‐related protein 8/14 or calprotectin), which plays an important role in maintaining the nutritional immunity in the host (Austermann, Spiekermann, & Roth, ; Corbin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term persistence of S. aureus might be facilitated by its ability to enter, replicate, and reside in professional phagocytes like macrophages (Li et al, 2017) and neutrophils (Gresham et al, 2000) and non-professional phagocytes as keratinocytes, fibroblasts, endothelial, and epithelial cells (Strobel et al, 2016), including also CF cells (Jarry & Cheung, 2006;Kahl et al, 2000). Furthermore, in some S. aureus CF isolates long-term persistence might be caused by enhanced production of nuclease, which was shown to facilitate bacterial escape from neutrophil extracellular traps (Herzog et al, 2019).…”
mentioning
confidence: 99%